2020
DOI: 10.1055/s-0040-1715832
|View full text |Cite
|
Sign up to set email alerts
|

A Risk Score for Predicting the Incidence of Hemorrhage in Critically Ill Neonates: Development and Validation Study

Abstract: The aim of the study was to develop and validate a prediction model for hemorrhage in critically ill neonates which combines rotational thromboelastometry (ROTEM) parameters and clinical variables. This cohort study included 332 consecutive full-term and preterm critically ill neonates. We performed ROTEM and used the neonatal bleeding assessment tool (NeoBAT) to record bleeding events. We fitted double selection least absolute shrinkage and selection operator logit regression to build our prediction model. Bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 33 publications
0
45
0
Order By: Relevance
“…Regarding the comment that we "did not provide clinical data to better characterize the severity of illness for patients enrolled" in our work, the study design and the inclusion criteria have been clearly reported in the Methods section. 2 We will be happy to provide specific additional clinical data if available in our dataset.…”
Section: Dear Editormentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the comment that we "did not provide clinical data to better characterize the severity of illness for patients enrolled" in our work, the study design and the inclusion criteria have been clearly reported in the Methods section. 2 We will be happy to provide specific additional clinical data if available in our dataset.…”
Section: Dear Editormentioning
confidence: 99%
“…We thank Dr. Ghirardello and colleagues 1 for their interest in our study, which introduced an easy-to-apply, rotational thromboelastometry-based, prediction model of hemorrhage in critically ill neonates. 2 Their letter gives us the opportunity to address their comments and provide clarifications to their assumptions.…”
mentioning
confidence: 99%
“…Prediction scores and bleeding assessment tools, which could help estimating the risk/benefit ratio of transfusions, are crucial for supporting clinical decisions and bleeding management in this vulnerable population [1][2][3][4]. Recently, our research group developed and published in the journal a multivariable prediction tool for 24hour bleeding risk in critically-ill neonates (Neonatal Bleeding Risk [NeoBRis] index) [5]. This assessment tool includes extrinsically activated rotational thromboelastometry parameters (EXTEM A10 and LI60 [amplitude recorded at 10 minutes and Lysis Index at 60 minutes, respectively]), platelet count and creatinine plasma levels and has demonstrated excellent performance (AUC: 0.908; 95% CI: 0.870-0.946).…”
mentioning
confidence: 99%
“…If this is indeed true, the percentage of IVH exceeds 50% in this latter population, which is extraordinarily high for the population included in the most recent study. 1 Third, the authors did not provide clinical data (i.e., Apgar score, need for mechanical ventilation and inotropes, SNAPPE score, mortality) to better characterize the severity of illness for the patients enrolled that could justify such a high incidence of IVH observed in their cohort.…”
mentioning
confidence: 99%
“…We read with interest the study by Sokou et al 1 and would like to make comments. The authors proposed a risk score for predicting hemorrhage of any grade in critically ill neonates within 24 hours of rotational thromboelastometry testing, using the Neonatal Bleeding Assessment Tool (NeoBAT) score.…”
mentioning
confidence: 99%